Modernisasi Maritim Berbasis Data di Sulawesi Selatan: Analisis Efisiensi Logistik, Kepatuhan AIS, dan Nilai Tambah Perikanan - Anwar Tahir; Parawansa Parawansa; Kaharto Kaharto; Reskyani Reskyani; Hein Frans Jules Katuuk (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the role of digital technology in supporting maritime development in South Sulawesi, focusing on port efficiency, maritime surveillance, fisheries supply chain digitalization, and policy as well as human resource capacity. A qualitative approach was employed through secondary data analysis obtained from the Central Bureau of Statistics, regional government reports, the Ministry of Marine Affairs and Fisheries, and relevant academic literature. The findings reveal that Makassar Port experienced an increase in cargo flow from 4.1 million tons in 2019 to 5.2 million tons in 2023, yet operational efficiency remains limited due to low adoption of digital systems. The implementation of the Automatic Identification System (AIS) and satellite monitoring reduced illegal fishing cases by 18% over the past two years, while supply chain digitalization through IoT and blockchain improved distribution efficiency by up to 25% at the pilot scale. The success of technology integration strongly depends on policy support, incentives, and maritime digital literacy programs. This study highlights that maritime modernization in South Sulawesi requires a systemic approach that integrates ports, surveillance, supply chains, and human resource development in a comprehensive manner.